A novel paperclip double-stranded RNA structure demonstrates clathrin-independent uptake in the mosquito Aedes aegypti. (December 2020) - Abbasi, Roohollah; Heschuk, Daniel; Kim, Brandon; Whyard, Steve
Abstract: RNA interference (RNAi) has become a widely used technique of knocking down a gene's expression in insects, but its efficacy in some species is limited by a reduced ability of the cells to take in and disperse the double-stranded RNA (dsRNA) throughout the cytoplasm. While RNA transport proteins such as SID-1 and its orthologues can facilitate dsRNA uptake in some invertebrate species, dsRNA uptake in many insects examined to date appears to be facilitated by clathrin-mediated endocytosis (CME). In this study, we used pharmacological inhibitors and RNAi-mediated knockdown of endocytic genes to provide evidence that CME is the primary means of dsRNA uptake in the mosquito Aedes aegypti . Inhibition of clathrin-mediated endocytosis was sufficient to supress uptake of short (21 nt) interfering RNAs (siRNAs), short (23 nt) hairpin RNAs (shRNAs), and long (>200 nt) dsRNA molecules in Aedes aegypti cultured cells and larvae. In contrast, we observed that short (23 nt) "paperclip" RNAs (pcRNAs), with partially closed ends, efficiently enter cells via a clathrin-independent pathway and effectively facilitate transcript knockdown. This alternative dsRNA structure may prove useful in insects generally considered recalcitrant to RNAi and in insect populations where resistance to RNAi-insecticides may arise through changes in dsRNA uptake mechanisms. Graphical abstract: Image 1 Highlights: Clathrin-mediated endocytosis is the primary route of cellular dsRNA uptake in Aedes aegypti . Inhibition of clathrin-mediated endocytosis results in reduced transcript silencing from siRNAs, shRNAs, and long dsRNAs. 'Paperclip' dsRNA structure (pcRNA) can enter cells treated with the clathrin inhibitor, chlorpromazine. PcRNA may be useful for insects recalcitrant or resistant to RNAi.